COMPARISON OF EFFICACY BETWEEN DEXMEDETOMIDINE AND PROPOFOL AFTER CORONARY ARTERY BYPASS GRAFT SURGERY - BANGASH, R; AHMAD, I; NAZ, U; ISLAM, MU; ZEB, A; SHAH, NA; SHABIR, A; SAJJAD, MW (Biological and Clinical Sciences Research Journal, 2024)
Postoperative management following coronary artery bypass graft (CABG) surgery is crucial for patient outcomes. Sedation plays a key role in recovery, with dexmedetomidine and propofol being commonly used agents. Evaluating the efficacy of these sedatives can help optimise postoperative care. Objective: To compare the effectiveness of dexmedetomidine and propofol in terms of pulmonary complications, mean mechanical ventilation time, and postoperative ICU and hospital stay in patients undergoing CABG surgery. Methods: A randomised controlled trial was conducted from October 1, 2023, to December 31, 2023, at a tertiary care hospital. Eighty patients scheduled for CABG surgery were randomised into two groups: Group A received dexmedetomidine, and Group B received propofol. Outcomes were assessed by measuring the incidence of pulmonary complications, mean mechanical ventilation time, length of postoperative ICU stay, and total hospital stay. Statistical analysis was performed using appropriate tests to compare the outcomes between the two groups, with significance set at P < 0.05. Results: Pulmonary complications occurred in 5% of patients in Group A, significantly lower than the 20% observed in Group B (P = 0.04). Group A’s mean mechanical ventilation time was 17.03 ± 3.46 hours, considerably shorter than Group B’s 23.20 ± 5.55 hours (P = 0.0001). Group A’s average postoperative ICU stay was 62.53 ± 15.10 hours, notably less than the 71.10 ± 14.06 hours for Group B (P = 0.01). Additionally, the mean hospital stay in Group A was 20.60 ± 1.99 days, significantly shorter than the 21.85 ± 3.11 days in Group B (P = 0.03). Conclusion: Dexmedetomidine demonstrates superior efficacy to propofol for patients undergoing CABG surgery, as evidenced by reduced pulmonary complications, shorter mechanical ventilation duration, and decreased postoperative ICU and hospital stays.